A dual functional fluorescent sensor for the detection of Al3+ and Zn2+ in different solvents. (23rd August 2019) - Xu, Yuankang; Wang, Hanyu; Zhao, Jinyan; Yang, Xiaofeng; Pei, Meishan; Zhang, Guangyou; Zhang, Yanxia
Abstract : A new fluorescent sensor, X, was designed and synthesized based on imidazo[2, 1- b ]thiazole and 2-hydroxy-1-naphthaldehyde, which could be used to detect Al 3+ in methanol buffer solution and detect Zn 2+ in ethanol buffer solution, respectively. Abstract : ( E )- N ′-((2-Hydroxynaphthalen-1-yl)methylene)imidazo[2, 1- b ]thiazole-6-carbohydrazide (X ), a new fluorescent sensor, was designed and synthesized based on imidazo[2, 1- b ]thiazole and 2-hydroxy-1-naphthaldehyde, which could be used to detect Al 3+ in methanol buffer solution and detect Zn 2+ in ethanol buffer solution with detection limits of 1.45 × 10 −7 M and 1.29 × 10 −8 M, respectively.X showed high sensitivity and selectivity towards Al 3+ and Zn 2+ in the presence of other metal ions. The fluorescence intensity ofX was reversible even after six cycles with the sequentially alternative addition of metal ions (Al 3+ and Zn 2+ ) and PPi, showing an efficient "off–on–off" fluorescence behavior. The complexation ratio ofX to Al 3+ and Zn 2+ was 1 : 1, which was proved by mass spectrometry and the B–H equation. The binding mode and sensing mechanism ofX with metal ions (Al 3+ and Zn 2+ ) were verified by DFT/TDDFT calculations using Gaussian 09 based on the B3LYP/6-31G(d) basis set.